Pengaruh Komunikasi dan Gaya Kepemimpinan Demokratis Terhadap Semangat Kerja Karyawan Pada PT. Minyak Kutus-Kutus Kabupaten Gianyar - Suari, Ni Kadek Candra Gita; Ayu Wimba, I Gusti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to find out the influence of communication and democratic leadership style on the morale of employees in PT. Kutus Oil- Kutus Gianyar Regency. This research was conducted at PT. Kutus-Kutus Oil Gianyar Regency. The population and sample number of 90 people. The sampling method used is a saturated sampling method. Data collection is done through questionnaires that have been tested for validity and reliability. The data analysis techniques used are classical assumption tests, reabilitias tests, validity tests, persianl and simultaneous tests with F tests and t tests, and multiple linear regression tests. Based on the results of the analysis found that communication has a positive and partially significant effect on the morale of employees. Democratic leadership styles have a positive and partially significant effect on morale. Then communication and democratic leadership style have a positive and significant effect on the morale of employees at PT. Miyak Kutus - Kutus Gianyar County. Suggestions to be able to increase employee morale by always involving employees both in work and able to provide fair and timely compensation.